Mortar compressive strength prediction model and method based on low-field magnetic resonance relaxation technology
The mortar compressive strength prediction model is constructed through low-field magnetic resonance relaxation technology, which solves the accuracy and safety of mortar compressive strength detection in ancient buildings, and realizes high-precision prediction of mortar compressive strength, meeting engineering needs And reduces the damage to the building by testing.
Patent Information
- Application Number
- CN202411360311.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to accurately and non-destructively test the compressive strength of mortars in important buildings and ancient buildings that have been in service for a long time. The traditional methods have negatively impacted the integrity and safety of the structure, and the accuracy and application range of the test results are limited.
Using the mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology, the mortar compressive strength prediction model is constructed by preparing standard mortar test pieces, low-field magnetic resonance relaxation test and pore structure analysis, combining Griffith fracture theory and rapid Relaxation theory, calculates the graded porosity and fitting parameters, and realizes accurate prediction of the compressive strength of the mortar.
It realizes rapid, simple and accurate inspection of the compressive strength of the mortar, meets engineering needs, reduces damage to the building, improves the accuracy and applicability of the inspection, and has important application value.
Smart Images

Figure CN119269238A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a compressive strength prediction model and method, in particular to a mortar compressive strength prediction model and method based on low-field magnetic resonance relaxation technology, and belongs to the technical field of building materials. Background Art
[0002] Mortar is made by mixing cementitious materials (cement, lime, gypsum, clay, etc.) and sand in a certain proportion and adding water. It is also called mortar when it does not contain sand. According to the type of cementitious materials, mortar is mainly divided into cement mortar, lime mortar, gypsum mortar, clay mortar and mixed mortar. It is an important component of building materials and is often used in masonry, plastering and grouting. Traditional mortar with lime, loess and other cementing materials is widely used in ancient buildings in my country. After thousands of years of wind and rain erosion, it is still hard and intact. The strength and durability of modern mortar and traditional mortar have a profound impact on the application effect of mortar / mortar in various engineering scenarios such as masonry structure construction and ancient building restoration. During construction and use, the compressive strength of mortar often varies significantly due to the influence of construction technology, environmental effects and human factors. In addition, during the long-term service of the building, the mortar gradually exchanges matter and energy with the environment, and its own mineral composition and pore structure will gradually change. The compressive strength and durability will also evolve over time and even decrease significantly, seriously affecting the safety and service life of the building structure.
[0003] At present, the test methods for mortar compressive strength mainly include: destructive compressive strength test using prism or cylinder specimens of specific size (such as cubes with a side length of 70.7 mm), micro-destructive pull-out method and needle penetration method, non-destructive ultrasonic rebound method, etc. In important buildings / structures in long-term service and key protected ancient buildings, the above detection and evaluation methods still have great technical difficulties and still need to be developed and improved in a targeted manner. For example, if mortar specimens are used for compressive strength testing, it is necessary to drill core samples of the existing structure to prepare specimens for compressive testing, which will have a serious negative impact on the integrity and safety of the structure and has poor feasibility; while for other detection methods such as pull-out method, penetration method and rebound method, the test point surface needs to be flat and smooth, and the test results depend on the strength measurement curve. There is room for improvement in the scope of application and the accuracy of the results. Therefore, the development of new test and evaluation methods for the compressive strength of mortar in important buildings / structures in long-term service and key protected ancient buildings not only meets the actual engineering needs, but also has important application value. Summary of the invention
[0004] The present invention aims to solve the problem of improving the feasibility and result accuracy of testing the mortar compressive strength of important buildings / structures in long-term service and key protected ancient buildings, and further proposes a mortar compressive strength prediction model and method based on low-field magnetic resonance relaxation technology.
[0005] The technical solution adopted by the present invention to solve the above problems is:
[0006] A method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology, wherein the method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology is achieved by the following steps:
[0007] S1: Preparation, curing and saturation treatment of standard mortar specimens. Select a certain type of cementitious material to prepare standard mortar specimens. The water-cement ratio and the mortar-sand ratio are determined by yourself. After all standard mortar specimens are demoulded, they are cured in the application environment for more than 28 days. After that, all standard mortar specimens are placed in a saturation equipment and saturated with water for more than 1 day.
[0008] S2: Low-field magnetic resonance relaxation test analysis of standard mortar specimens, including test preparation, parameter setting, low-field magnetic resonance relaxation signal acquisition, calibration water testing and determination of pore size distribution of standard mortar specimens;
[0009] S3: Compressive strength test of standard mortar specimens, using a compression tester to test the compressive strength of each standard mortar specimen;
[0010] S4: Determine the relationship model between the standard mortar specimen and the pore structure, including calculation of graded porosity, model construction and fitting parameter determination.
[0011] Furthermore, the low-field magnetic resonance relaxation test analysis of the standard mortar specimen described in S2 specifically includes:
[0012] S2.1: Test preparation: Wrap the standard mortar specimen tightly with plastic wrap and then place it in the sample chamber of the low-field magnetic resonance relaxation test equipment;
[0013] S2.2: Setting parameters: Perform low-field magnetic resonance relaxation test using CPMG pulse sequence and set test parameters;
[0014] S2.3: Low-field magnetic resonance relaxation signal acquisition: Use the CPMG pulse sequence to perform low-field magnetic resonance relaxation tests on each standard mortar specimen to obtain the pulse echo signal M(τ). The expression of M(τ) is as follows:
[0015]
[0016] In formula (1), the pores inside the mortar are divided into J groups, T 2i is the transverse relaxation time of the pore water in the i-th group (i=1,2,...,J), in seconds, f i is the volume fraction of the pore water in the i-th group, dimensionless, V i is the volume of the pore water in group i, in m 3 , V 0is the total volume of all pore water, in m 3 , M 0 It is the total signal of pore water obtained by using the commonly used multi-exponential fitting algorithm of low-field magnetic resonance relaxation signal, and the unit is μV. i (T 2i ) is the transverse relaxation time spectrum of each group of pore water obtained using the multi-exponential inversion algorithm;
[0017] S2.4: Calibration water test: Use the same CPMG test method to test the water with a concentration of 1%wt and a water content of m wb The copper sulfate solution was tested and analyzed for low-field magnetic resonance relaxation to obtain its relaxation signal M wb Since the total relaxation signal is strictly proportional to the water mass, the pore water content of the standard mortar specimen is m w The expression is as follows:
[0018]
[0019] S2.5: Determination of pore size distribution of standard mortar specimen: Take another standard mortar specimen and place it at 23% relative humidity for more than 28 days. Use the low-field magnetic resonance relaxation test of the Hahn spin echo sequence to obtain the surface relaxation strength ρ of the mortar specimen. 2 According to the rapid relaxation theory, the transverse relaxation time T of the standard mortar specimen is 2i Converted to the equivalent radius r of a cylindrical pore i .
[0020] Furthermore, the fast relaxation theory is the equivalent radius r of the pores in the i-th group i The transverse relaxation time T of its internal water 2i Proportional, the expression is as follows:
[0021] r i =2ρ 2 T 2i (3)
[0022] Furthermore, the determination of the relationship model between the standard mortar specimen and the pore structure described in S4 specifically includes:
[0023] S4.1: Calculate the graded porosity: According to the pore size distribution of the standard mortar specimen, calculate the graded porosity p of pores r>10nm and r<10nm respectively. >10 With p <10 ;
[0024] S4.2: Model construction: When r>10nm, the effect of pores on the compressive strength σ of mortar is expressed according to Griffith fracture theory, and only p is considered >10Elastic modulus E of mortar 0 and fracture surface energy γ 0 The expression of compressive strength prediction model is as follows:
[0025]
[0026] In formula (4), r b is the half width of the crack when the mortar fails, the unit is m, n is p >10 Fracture surface energy γ 0 The influencing parameters of
[0027] When r < 10 nm, the pores only affect the strength of the mortar matrix and are related to 1-p <10 The expression of the compressive strength prediction model is modified as follows:
[0028]
[0029] In formula (5), p >10 With p <10 There are 2 variables in total, and n, E 0 , γ 0 、r b There are 4 fitting parameters in total. However, for different mortar specimens, the last 3 of these 4 fitting parameters can be regarded as 1 fitting parameter, namely E 0 γ 0 / r b . The fitting parameter E 0 γ 0 / r b The combination is the fitting parameter x, and the fitting parameter n is replaced by the fitting parameter y;
[0030] S4.3: Determination of fitting parameters: Based on the measured compressive strength and graded porosity p of the standard mortar specimens >10 、p <10 , fitting to obtain the x and y values in the model, ensuring the square of the correlation coefficient R 2 >0.99.
[0031] Furthermore, in S4.2, when r < 10 nm, the compressive strength prediction model can be optimized as follows:
[0032]
[0033] Furthermore, the test parameters described in S2.2 include: echo interval, number of echoes, waiting time, number of scans, sampling time interval, and number of acquisition points.
[0034] Furthermore, the size of the standard mortar specimen described in S1 is 20 mm×20 mm×50 mm.
[0035] Furthermore, the application environment described in S1 is a dry environment, a high humidity environment or an underwater environment.
[0036] The mortar compressive strength prediction method based on low-field magnetic resonance relaxation technology first performs low-field magnetic resonance relaxation test analysis on the mortar specimens to be tested, and then predicts the compressive strength of the mortar specimens to be tested using a compressive strength prediction model obtained by a mortar compressive strength prediction model construction method based on low-field magnetic resonance relaxation technology.
[0037] Furthermore, the low-field magnetic resonance relaxation test analysis of the mortar specimen to be tested is achieved by the following steps:
[0038] S1a: Drilling of mortar specimens to be tested: Drill mortar specimens to be tested with a size less than or equal to the size of standard mortar specimens from various parts of the buildings and structures to be tested;
[0039] S2a: Saturation treatment of the mortar specimen to be tested: Place the mortar specimen to be tested in a saturation device and saturate it with water for more than 1 day;
[0040] S3a: Low-field magnetic resonance relaxation test of the mortar specimen to be tested: Wrap the mortar specimen to be tested tightly with plastic wrap, and then put it into the sample chamber of the low-field nuclear magnetic resonance relaxation test equipment for testing. The test parameters are consistent with those when testing the standard mortar specimen;
[0041] S4a: Low-field magnetic resonance relaxation signal acquisition: The CPMG pulse sequence is used to perform low-field magnetic resonance relaxation tests on each mortar specimen to be tested, and its pulse echo signal M(τ) can be obtained. 测 ;
[0042] S5a: Determination of pore size distribution of the mortar specimen to be tested: The relaxation time spectrum f of each mortar specimen to be tested is calculated using the fast relaxation theory. i (T 2i ) 测 Convert to pore size distribution f i (r i ) 测 , surface relaxation intensity ρ 2 Keep consistent with testing standard mortar specimens;
[0043] S6a: Calculate the graded porosity of the mortar specimen to be tested: According to the pore size distribution of the mortar specimen to be tested, calculate the graded porosity p of pores r>10nm and r<10nm >10测 With p <10测 .
[0044] The beneficial effects of the present invention are:
[0045] Aiming at the different problems existing in different mortar compressive strength test methods in important buildings / structures in long-term service and key protected ancient buildings, the present invention proposes a model and method for quickly testing and characterizing the pore structure characteristics of mortar and accurately predicting its compressive strength using low-field magnetic resonance relaxation technology. The mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology has strong applicability, good stability, and extremely high fitting accuracy. The mortar compressive strength prediction method based on low-field magnetic resonance relaxation technology can accurately predict the mortar compressive strength while minimizing damage to the building, meeting the requirements of fast, simple, large-scale, and accurate testing, and achieving the technical goal of reducing costs and increasing efficiency. It not only meets actual engineering needs, but also has important application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 It is a schematic flow chart of a method for predicting mortar compressive strength based on low-field magnetic resonance relaxation technology of the present invention;
[0047] Figure 2 This is a schematic diagram of a typical pore size distribution of cement mortar obtained by testing using low-field magnetic resonance relaxation technology in the present invention;
[0048] Figure 3 It is a comparison chart of the compressive strength measured by the standard cement mortar of the present invention and the compressive strength predicted by the fitting model. DETAILED DESCRIPTION
[0049] Specific implementation method 1: Combination Figure 1-3 The present embodiment is described. The method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology described in the present embodiment is achieved by the following steps:
[0050] S1: Preparation, curing and saturation treatment of standard mortar specimens. Select a certain type of cementitious material to prepare standard mortar specimens. The water-cement ratio and mortar-sand ratio are determined by yourself. The preferred size of the standard mortar specimen is 20mm×20mm×50mm, which is convenient for the testing and analysis of standard mortar specimens, as well as the extraction and testing analysis of the size of the mortar specimens to be tested. After demolding all standard mortar specimens, they are cured in the application environment for more than 28 days. The application environment is a dry environment, a high humidity environment or an underwater environment. The effects of dry, high humidity and underwater environments on mortar are different. Therefore, when selecting and using mortar, it is necessary to comprehensively consider and select according to the specific application environment. After that, all standard mortar specimens are placed in a saturated device and saturated with water for more than 1 day.
[0051] Specifically, white silicate cement with a grade of 42.5 and triterpenoid saponin-type air-entraining agent were used to prepare standard mortar specimens. The water-cement ratio is 0.4, and the mortar-sand ratio is 1:2. The air-entraining agent is added, and its mass fraction is 0‰, 0.5‰, 1.0‰ and 1.5‰ of the cement mass, respectively. There are 4 groups in total, and each group includes 10 standard mortar specimens. After the raw materials are evenly mixed, they are cast into mortar specimens with a size of 20mm×20mm×50mm, and demolded after 24 hours of film curing. After all standard mortar specimens are demolded, they are placed in a curing box filled with saturated lime water for 56 days, and the curing temperature is maintained at 20±2℃. After the curing is completed, all standard mortar specimens are placed in a high-pressure saturated water equipment, and the saturated water pressure is maintained at above 15MPa for 3 days.
[0052] S2: Low-field magnetic resonance relaxation test analysis of standard mortar specimens, the low-field magnetic resonance relaxation test analysis of standard mortar specimens is achieved by the following steps:
[0053] S2.1: Test preparation: After saturation, wrap the standard mortar specimen tightly with plastic wrap and then place it in the sample chamber of the low-field magnetic resonance relaxation test equipment.
[0054] S2.2: Setting parameters: Perform low-field magnetic resonance relaxation test using CPMG pulse sequence and set test parameters, including echo time, echo count, repetition time, scan times, dwell time, and samples.
[0055] Specifically, the key parameters for testing using the CPMG pulse sequence can be set as follows: echo interval τ e The time interval is set to 60 μs, the number of echoes N is set to 50,000, the waiting time is set to 15 s, the number of scans is set to 300, and the number of acquisition points is set to 4. Except for the echo interval, the other parameters can be flexibly adjusted to make the signal-to-noise ratio of the obtained relaxation data higher than 300.
[0056] S2.3: Low-field magnetic resonance relaxation signal acquisition: Use the CPMG pulse sequence to perform low-field magnetic resonance relaxation tests on each standard mortar specimen to obtain the pulse echo signal M(τ). The expression of M(τ) is as follows:
[0057]
[0058] In formula (1), the pores inside the mortar are divided into J groups, T 2i is the transverse relaxation time of the pore water in the i-th group (i=1,2,...,J), in seconds, f i is the volume fraction of the pore water in the i-th group, dimensionless, V iis the volume of the pore water in group i, in m 3 , V 0 is the total volume of all pore water, in m 3 , M 0 is the total signal of pore water obtained by using the commonly used multi-exponential inversion algorithm, in μV, f i (T 2i ) is the transverse relaxation time spectrum of each group of pore water obtained using the multi-exponential inversion algorithm;
[0059] S2.4: Calibration water test: Use the same CPMG test method as S2.3 to test the water with a concentration of 1%wt and a water content of m wb The copper sulfate solution was tested and analyzed by low-field magnetic resonance relaxation. Specifically, the water content was m wb (Take 10g) of copper sulfate solution for low-field magnetic resonance relaxation test and analysis,
[0060] Get its relaxation signal M wb Since the total relaxation signal is strictly proportional to the water mass, the pore water content of the standard mortar specimen is m w The expression is as follows:
[0061]
[0062] Specifically, the same CPMG test method was used to test the concentration of 1% wt and the water content of m wb (Take 10g) of copper sulfate solution for relaxation test and analysis to obtain its relaxation signal M wb . Because the total relaxation signal is strictly proportional to the water mass.
[0063] S2.5: Determination of pore size distribution of standard mortar specimen: Take another standard mortar specimen and place it at 23% relative humidity for more than 28 days. Use the low-field magnetic resonance relaxation test of the Hahn spin echo sequence to obtain the surface relaxation strength ρ of the mortar specimen. 2 According to the rapid relaxation theory, the transverse relaxation time T of the standard mortar specimen is 2i Converted to the equivalent radius r of a cylindrical pore i .
[0064] Specifically, another standard mortar specimen was placed at 23% RH for 56 days to ensure that a monolayer of water molecules was adsorbed on the pore wall surface. The surface relaxation intensity ρ was obtained by low-field magnetic resonance relaxation test using Hahn spin echo sequence. 2 , can be taken as 1.8nm / ms. According to the fast relaxation theory, the equivalent radius r of the pores in the i-th group i The transverse relaxation time T of its internal water 2i The relaxation time T of the standard mortar specimen can be calculated using the following formula:2i Converted to pore equivalent radius r i , that is, the relaxation time spectrum f i (T 2i ) is converted to pore size distribution f i (r i ),like Figure 2 As shown, the fast relaxation theory expression is as follows:
[0065] r i =2ρ 2 T 2i (3)
[0066] S3: Compressive strength test of standard mortar specimens, using a compression-flexure tester to test the compressive strength of each standard mortar specimen. Specifically, a YAW-300 microcomputer fully automatic cement compression-flexure tester was used to test the compressive strength of each standard mortar specimen. The specimen size was 20mm×50mm and the side was compressed. The loading rate during the test was fixed at 0.2kN / s.
[0067] 2. S4: Determine the relationship model between the standard mortar specimen and the pore structure, wherein determining the relationship model between the standard mortar specimen and the pore structure specifically includes:
[0068] S4.1: Calculate the graded porosity: According to the pore size distribution of the standard mortar specimen, calculate the graded porosity p of pores r>10nm and r<10nm respectively. >10 With p <10 Specifically, the volume of each standard mortar specimen was tested by the buoyancy method, and then the graded porosity p of pores with r>10nm and r<10nm was calculated based on their pore size distribution and r=10nm as the boundary. >10 With p < 10.
[0069] S4.2: Model construction: When r>10nm, the effect of pores on the compressive strength σ of mortar is expressed according to Griffith fracture theory, and only p is considered >10 Mortar elastic modulus E 0 and fracture surface energy γ 0 The expression of compressive strength prediction model is as follows:
[0070]
[0071] In formula (4), r b is the half width of the crack when the mortar fails, the unit is m, n is p >10 Fracture surface energy γ 0 The influencing parameters of
[0072] When r < 10 nm, the pores only affect the strength of the mortar matrix and are related to 1-p<10 The expression of the compressive strength prediction model is modified as follows:
[0073]
[0074] In formula (5), p >10 With p <10 There are 2 variables in total, and n, E 0 , γ 0 、r b There are 4 fitting parameters in total. However, for different mortar specimens, the last 3 of these 4 fitting parameters can be regarded as 1 fitting parameter, namely E 0 γ 0 / r b . The fitting parameter E 0 γ 0 / r b The combination is the fitting parameter x, and the fitting parameter n is replaced by the fitting parameter y;
[0075] After simplification, when r<10nm, the compressive strength prediction model can be optimized as follows:
[0076]
[0077] S4.3: Determination of fitting parameters: Based on the measured compressive strength and graded porosity p of the standard mortar specimens >10 、p <10 , fitting to obtain the x and y values in the model, ensuring the square of the correlation coefficient R 2 >0.99. Figure 3 As shown in the figure, by comparing the compressive strength of the standard mortar specimen with the compressive strength predicted by its pore structure, it can be seen that the model has strong applicability, good stability and extremely high fitting accuracy.
[0078] The present invention also proposes a method for predicting the compressive strength of mortar based on low-field magnetic resonance relaxation technology. First, a low-field magnetic resonance test and analysis is performed on the mortar specimen to be tested, and then the compressive strength of the mortar specimen to be tested is predicted using a compressive strength prediction model obtained by the method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology.
[0079] The low-field magnetic resonance relaxation test analysis of the mortar specimen to be tested is achieved by the following steps:
[0080] S1a: Drilling of mortar specimens to be tested: Drill mortar specimens to be tested with a size less than or equal to the size of standard mortar specimens from various parts of the buildings and structures to be tested; specifically, drill mortar specimens to be tested with a size of 20mm×20mm×50mm.
[0081] S2a: Saturation treatment of the mortar specimen to be tested: Place the mortar specimen to be tested in a saturation device and saturate it with water for more than 1 day. Specifically, the saturation pressure is maintained above 15 MPa and the saturation is carried out for 3 days.
[0082] S3a: Low-field magnetic resonance relaxation test of the mortar specimen to be tested: Wrap the mortar specimen to be tested tightly with plastic wrap, and then put it into the sample chamber of the low-field magnetic resonance relaxation test equipment for testing. The test parameters are consistent with those when testing the standard mortar specimen;
[0083] S4a: Low-field magnetic resonance relaxation signal acquisition: The CPMG pulse sequence is used to perform low-field magnetic resonance relaxation tests on each mortar specimen to be tested, and its pulse echo signal M(τ) can be obtained. 测 ;
[0084] S5a: Determination of pore size distribution of the mortar specimen to be tested: The relaxation time spectrum f of the mortar specimen to be tested is converted into i (T 2i ) 测 Convert to pore size distribution f i (r i ) 测 , surface relaxation intensity ρ 2 It is consistent with the test of standard mortar specimens. Specifically, the surface relaxation strength ρ 2 1.8nm / ms is acceptable;
[0085] S6a: Calculate the graded porosity of the mortar specimen to be tested: According to the pore size distribution of the mortar specimen to be tested, calculate the graded porosity p of pores r>10nm and r<10nm >10测 With p <10测 ;
[0086] like Figure 1 As shown, combined with the method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology, the mortar compressive strength prediction method based on low-field magnetic resonance relaxation technology can be specifically implemented through the following steps:
[0087] S1: Preparation, curing and saturation treatment of standard mortar specimens:
[0088] S1.1: Use white silicate cement with a grade of 42.5 and triterpenoid saponin-type air-entraining agent to prepare standard mortar specimens. The water-cement ratio is 0.4, and the mortar-sand ratio is 1:2. The air-entraining agent is added, and its mass fraction is 0‰, 0.5‰, 1.0‰ and 1.5‰ of the cement mass, respectively. There are 4 groups in total, and each group includes 10 standard mortar specimens. After the raw materials are mixed evenly, they are cast into mortar specimens with a size of 20mm×20mm×50mm, and demolded after 24 hours of film curing;
[0089] S1.2: Curing of standard mortar specimens: After demoulding, all standard mortar specimens were placed in a curing box filled with saturated lime water for 56 days, and the curing temperature was maintained at 20±2℃;
[0090] S1.3: Saturation treatment of standard mortar specimens: After the curing is completed, all standard mortar specimens are placed in a high-pressure saturation device, with the saturation pressure maintained above 15 MPa, and saturated for 3 days;
[0091] S2: Low-field magnetic resonance relaxation test analysis of standard mortar specimens:
[0092] S2.1: Low-field magnetic resonance relaxation test of standard mortar specimens: After saturation, wrap the standard mortar specimens tightly with plastic wrap and place them in the sample compartment of the low-field nuclear magnetic resonance relaxation test equipment. Use the CPMG pulse sequence for testing. The key parameters can be set as follows: echo interval τ e The time interval is set to 60 μs, the number of echoes N is set to 50,000, the waiting time is set to 15 s, the number of scans is set to 300, and the number of acquisition points is set to 4. Except for the echo interval, the other parameters can be flexibly adjusted to make the signal-to-noise ratio of the obtained relaxation data higher than 300.
[0093] S2.2: Low-field magnetic resonance signal acquisition: The CPMG pulse sequence is used to perform low-field magnetic resonance relaxation tests on each standard mortar specimen to obtain its pulse echo signal M(τ);
[0094]
[0095] S2.3: Low-field magnetic resonance relaxation signal analysis: The internal pores of cement mortar can be divided into J groups. The transverse relaxation time and volume fraction of pore water in group i (i = 1, 2, ..., J) are T 2i and f i , the total signal of pore water M can be obtained by using the multi-exponential inversion algorithm 0 and the transverse relaxation time spectra of each group of pore water f i (T 2i );
[0096] S2.4: Calibration water test: Use the same CPMG test method to test the water with a concentration of 1%wt and a water content of m wb (10 g) of copper sulfate solution is used for relaxation test and analysis to obtain its relaxation signal M wb Since the total relaxation signal is strictly proportional to the water mass, the pore water content of the standard mortar specimen is m w for
[0097]
[0098] S2.5: Determination of pore size distribution of standard mortar specimen: Take another standard mortar specimen and place it at 23% relative humidity for 56 days to ensure that a monolayer of water molecules is adsorbed on the pore wall surface. The surface relaxation intensity ρ can be obtained by low-field magnetic resonance relaxation test using Hahn spin echo sequence. 2 , can be taken as 1.8nm / ms. According to the fast relaxation theory, the cylindrical equivalent radius r of the pores in the i-th group i The transverse relaxation time T of its internal water 2i The relaxation time T of the standard mortar specimen can be calculated using the following formula: 2i Converted to pore equivalent radius r i , that is, the relaxation time spectrum f i (T 2i ) is converted to pore size distribution f i (r i ),Right now Figure 2 ;
[0099] r i =2ρ 2 T 2i
[0100] S3: Compressive strength test of standard mortar specimens: The compressive strength of each standard mortar specimen was tested using a YAW-300 microcomputer fully automatic cement compression and folding tester. The specimen size was 20mm×50mm and the side was compressed. The loading rate during the test was fixed at 0.2kN / s.
[0101] S4: Determine the relationship model between the standard mortar specimen and the pore structure:
[0102] S4.1: Calculate the graded porosity: Use the buoyancy method to test the volume of each standard mortar specimen, and then calculate the graded porosity p of pores r>10nm and r<10nm based on their pore size distribution, with r=10nm as the boundary. >10 With p <10 ;
[0103] S4.2: Model construction: The effect of r>10nm pores on the compressive strength σ of mortar can be explained by Griffith fracture theory, and p >10 Mortar elastic modulus E 0 and fracture surface energy γ 0 The compressive strength and p >10 The following relationship exists:
[0104]
[0105] The pores with r < 10 nm only affect the strength of the mortar matrix and are not related to 1-p <10 The final model is confirmed as follows:
[0106]
[0107] The fitting parameter E 0 γ 0 / r b The combination is the fitting parameter x, and the fitting parameter n is replaced by the fitting parameter y. After simplification, the model can be transformed into the following formula:
[0108]
[0109] S4.3: Determination of fitting parameters: Based on the measured compressive strength and graded porosity p of the standard mortar specimens >10 、p <10 , fitting to obtain the x and y values in the model, ensuring the square of the correlation coefficient R 2 >0.99. Compare the compressive strength of the standard mortar specimen with the compressive strength predicted by its pore structure, such as Figure 3 As shown, it can be seen that the model has strong applicability, good stability and extremely high fitting accuracy.
[0110] S5: Low-field magnetic resonance test and analysis of the mortar specimen to be tested;
[0111] S5.1: Drilling of mortar specimens to be tested: Drill mortar specimens to be tested with a size of 20mm×20mm×50mm from various parts of the buildings and structures to be tested;
[0112] S5.2: Saturation treatment of the mortar specimen to be tested: Place the mortar specimen to be tested in a high-pressure saturation device, keep the saturation pressure above 15MPa, and saturate for 3 days;
[0113] S5.3: Low-field magnetic resonance relaxation test of the mortar specimen to be tested: Wrap the mortar specimen to be tested tightly with plastic wrap, and then put it into the sample chamber of the low-field magnetic resonance relaxation test equipment for testing. The test parameters should be consistent with those when testing the standard mortar specimen;
[0114] S5.4: Low-field magnetic resonance relaxation signal acquisition: Use the CPMG pulse sequence to perform low-field magnetic resonance relaxation test on each mortar specimen to be tested, and obtain its pulse echo signal M(τ);
[0115] S5.5: Calibration water test: Use the same CPMG test method to test the water with a concentration of 1%wt and a water content of m wb (Take 10g) of copper sulfate solution for relaxation test and analysis to obtain its relaxation signal M wb Since the total relaxation signal is strictly proportional to the water mass, the pore water content of the standard mortar specimen is m w for
[0116]
[0117] S5.6: Determination of pore size distribution of the mortar specimen to be tested: The relaxation time spectrum f of the mortar specimen to be tested is calculated using the following formula: i (T 2i ) 测 Convert to pore size distribution f i (r i ) 测 , surface relaxation intensity ρ 2 1.8nm / ms is acceptable;
[0118] r i =2ρ 2 T 2i
[0119] S5.7: Calculate the graded porosity of the mortar specimen to be tested: According to the pore size distribution of the mortar specimen to be tested, calculate the graded porosity p of pores with r>10nm and r<10nm >10测 With p <10测 ;
[0120] S6: Prediction of compressive strength of the mortar specimen to be tested; based on the fitting model and the graded porosity p of the mortar specimen to be tested >10 With p <10 , the compressive strength of the corresponding mortar specimen to be tested can be calculated, and the prediction effect is excellent.
[0121] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent replacement and improvement made to the above embodiments without departing from the content of the technical solution of the present invention, based on the technical essence of the present invention, within the spirit and principles of the present invention, still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology, characterized in that: The method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology is achieved by the following steps: S1: Preparation, curing and saturation treatment of standard mortar specimens. Select a certain type of cementitious material to prepare standard mortar specimens. The water-cement ratio and the mortar-sand ratio are determined by yourself. After all standard mortar specimens are demoulded, they are cured in the application environment for more than 28 days. After that, all standard mortar specimens are placed in a saturation equipment and saturated with water for more than 1 day. S2: Low-field magnetic resonance relaxation test analysis of standard mortar specimens, including test preparation, parameter setting, low-field magnetic resonance relaxation signal acquisition, calibration water testing and determination of pore size distribution of standard mortar specimens; S3: Compressive strength test of standard mortar specimens, using a compression tester to test the compressive strength of each standard mortar specimen; S4: Determine the relationship model between the standard mortar specimen and the pore structure, including calculation of graded porosity, model construction and fitting parameter determination.
2. The method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology according to claim 1, characterized in that: The low-field magnetic resonance relaxation test analysis of the standard mortar specimen described in S2 specifically includes: S2.1: Test preparation: Wrap the standard mortar specimen tightly with plastic wrap and then place it in the sample chamber of the low-field magnetic resonance relaxation test equipment; S2.2: Setting parameters: Perform low-field magnetic resonance relaxation test using CPMG pulse sequence and set test parameters; S2.3: Low-field magnetic resonance relaxation signal acquisition: Use the CPMG pulse sequence to perform low-field magnetic resonance relaxation tests on each standard mortar specimen to obtain the pulse echo signal M(τ). The expression of M(τ) is as follows: In formula (1), the pores inside the mortar are divided into J groups, T 2i is the transverse relaxation time of the pore water in the i-th group (i=1,2,...,J), in seconds, f i is the volume fraction of the pore water in the i-th group, dimensionless, V i is the volume of the pore water in group i, in m 3 , V0 is the total volume of all pore water, in m 3 M0 is the total signal of pore water obtained by multi-exponential fitting algorithm of low-field magnetic resonance relaxation signal, and the unit is μV. i (T 2i ) is the transverse relaxation time spectrum of each group of pore water obtained using the multi-exponential inversion algorithm; S2.4: Calibration water test: Use the same CPMG test method as S2.3 to test the water with a concentration of 1%wt and a water content of m wb The copper sulfate solution was tested and analyzed by low-field magnetic resonance relaxation to obtain its relaxation signal M wb Since the total relaxation signal is strictly proportional to the water mass, the pore water content of the standard mortar specimen is m w The expression is as follows: S2.5: Determination of pore size distribution of standard mortar specimen: Take another standard mortar specimen and place it at a relative humidity of 23% for more than 28 days. Use the low-field magnetic resonance relaxation test of the Hahn spin echo sequence to obtain the surface relaxation intensity ρ2 of the mortar specimen. According to the fast relaxation theory, the transverse relaxation time T 2i Converted to the equivalent radius r of a cylindrical pore i .
3. The method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology according to claim 2, characterized in that: The fast relaxation theory is the equivalent radius r of the pores in the i-th group i The transverse relaxation time T of its internal water 2i Proportional, the expression is as follows: r i =2ρ2T 2i (3) 4. The method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology according to claim 3 is characterized in that: The model for determining the relationship between the standard mortar specimen and the pore structure described in S4 specifically includes: S4.1: Calculate the graded porosity: According to the pore size distribution of the standard mortar specimen, calculate the graded porosity p of pores r>10nm and r<10nm respectively. >10 With p <10 ; S4.2: Model construction: When r>10nm, the effect of pores on the compressive strength σ of mortar is expressed according to Griffith fracture theory, and only p is considered >10 The influence on the mortar elastic modulus E0 and fracture surface energy γ0, the expression of the compressive strength prediction model is as follows: In formula (4), r b is the half width of the crack when the mortar specimen is damaged, the unit is m, n is p >10 Influencing parameters on fracture surface energy γ0; When r < 10 nm, the pores only affect the strength of the mortar matrix and are related to 1-p <10 The expression of the compressive strength prediction model is modified as follows: In formula (5), p >10 With p <10 There are 2 variables in total, as well as n, E0, γ0, r b There are 4 fitting parameters in total. However, for different mortar specimens, the last 3 of these 4 fitting parameters can be regarded as 1 fitting parameter, namely E0γ0 / r b . The fitting parameter E0γ0 / r b The combination is the fitting parameter x, and the fitting parameter n is replaced by the fitting parameter y; S4.3: Determination of fitting parameters: Based on the measured compressive strength and graded porosity p of the standard mortar specimens >10 、p <10 , fitting to obtain the x and y values in the model, ensuring the square of the correlation coefficient R 2 >0.
99.
5. The method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology according to claim 4, characterized in that: The compressive strength prediction model described in S4.2 is finally optimized as:
6. The method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology according to claim 2, characterized in that: The test parameters described in S2.2 include: echo interval, number of echoes, waiting time, number of scans, sampling time interval, and number of acquisition points.
7. The method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology according to claim 1, characterized in that: The size of the standard mortar specimen described in S1 is 20 mm × 20 mm × 50 mm.
8. The method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology according to claim 1, characterized in that: The application environment described in S1 is a dry environment, a high humidity environment or an underwater environment.
9. A method for predicting mortar compressive strength based on low-field magnetic resonance relaxation technology, characterized in that: First, a low-field magnetic resonance relaxation test is performed on the mortar specimen to be tested, and then the compressive strength of the mortar specimen to be tested is predicted using a compressive strength prediction model obtained by the method for constructing a mortar compressive strength prediction model based on low-field magnetic resonance relaxation technology as described in any one of claims 1 to 8.
10. The method for predicting mortar compressive strength based on low-field magnetic resonance relaxation technology according to claim 9, characterized in that: The low-field magnetic resonance relaxation test analysis of the mortar specimen to be tested is achieved by the following steps: S1a: Drilling of mortar specimens to be tested: Drill mortar specimens to be tested with a size less than or equal to the size of standard mortar specimens from various parts of the buildings and structures to be tested; S2a: Saturation treatment of the mortar specimen to be tested: Place the mortar specimen to be tested in a saturation device and saturate it with water for more than 1 day; S3a: Low-field magnetic resonance relaxation test of the mortar specimen to be tested: Wrap the mortar specimen to be tested tightly with plastic wrap, and then put it into the sample chamber of the low-field magnetic resonance relaxation test equipment for testing. The test parameters are consistent with those when testing the standard mortar specimen; S4a: Low-field magnetic resonance relaxation signal acquisition: The CPMG pulse sequence is used to perform low-field magnetic resonance relaxation tests on each mortar specimen to be tested, and its pulse echo signal M(τ) can be obtained. 测 ; S5a: Determination of pore size distribution of the mortar specimen to be tested: The relaxation time spectrum f of each mortar specimen to be tested is calculated using the fast relaxation theory. i (T 2i ) 测 Convert to pore size distribution f i (r i ) 测 , the surface relaxation strength ρ2 is consistent with that when testing standard mortar specimens; S6a: Calculate the graded porosity of the mortar specimen to be tested: According to the pore size distribution of the mortar specimen to be tested, calculate the graded porosity p of pores r>10nm and r<10nm >10测 With p <10测 .
Citation Information
Cited By
Cement-based material undisturbed hole measuring method based on low-field magnetic resonance longitudinal relaxation technology
CN120064362A